2003
DOI: 10.2116/analsci.19.871
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective and Efficient Membrane Transport of Silver as AgBr-2 Ion Using K+-decyl-18-crown-6 as Carrier

Abstract: Potassium-decyl-18-crown-6 was used as a highly selective and efficient carrier for uphill transport of silver as AgBr2 -complex ion through a chloroform bulk liquid membrane. When thiosulfate anion was used as a metal ion acceptor in the receiving phase the amounts of silver transported across the liquid membrane after 120 and 180 min were 87.0 ± 1.8% and 96.0 ± 1.9%, respectively. The selectivity and efficiency of silver transport from aqueous solution containing Cu 2+ , Zn 2+ , Ni 2+ , Cd 2+ , Pb 2+ and Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Only a few reports on the membrane transport mechanism of silver ions have been published, but they do not provide complete understanding of the topic. Highly selective and efficient membrane transport of silver as AgBr 2 − using K + -decyl-18-crown-6 as a carrier was reported (Zolgharnein et al, 2003). However, no report on the transport mechanism of AgNPs has been released.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few reports on the membrane transport mechanism of silver ions have been published, but they do not provide complete understanding of the topic. Highly selective and efficient membrane transport of silver as AgBr 2 − using K + -decyl-18-crown-6 as a carrier was reported (Zolgharnein et al, 2003). However, no report on the transport mechanism of AgNPs has been released.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that silver may get imported through the cell membrane as the anionic form of AgBr 2 [1]. However, no studies have ever addressed the electronic structure of the lowest (ligand-field) states of the neutral molecule, which can be formed by the Ag + Br 2 ?…”
Section: Introductionmentioning
confidence: 99%